Buffalo production in small scale and commercial farms in Bangladesh (Asian Journal of Medical and Biological Research, 2021)
The present study was aimed to compare the production status and management practices of crossbred buffaloes between small scale and commercial farms in Bangladesh. The data were collected through personal interview from the individual respondent. The study revealed that duration of buffalo rearing was mostly practiced for more than two years. Various types of feed ingredients including rice straw, wheat straw, green grass, concentrate feed, cultivated fodder, tree leaves and unconventional feed resources were used for feeding buffaloes. In small scale, 83.34% farmers fed their buffalo in a group and 75% buffaloes reared under semi-intensive system while all buffaloes practiced individual feeding and reared under intensive system in commercial farms. The daily milk production, lactation length and yield of dam and birth weight of calves significantly (p